The contemporary intellectual crisis and lack of clear perception of science and scientific thinking: the challenge of the Quran - Ali, Mohd Mumtaz (Universiti Sains Islam Malaysia (USIM), 2015)
It seems that the contemporary world is suffering from an acute intellectual crisis and lack of clear perception of science and scientific thinking. This is visible everywhere in political, economic, technological, social and educational domains of life. Since the beginning of the third millennium, we have been witnessing protests, unrest, unrestricted local wars and natural calamities. The current empirical realities and evidence are manifestations of the intellectual crisis and lack of clear perception of science and scientific thinking. It is, therefore, contended in this paper that there is an urgent need to revisit the so-called modern Western science and its dominant paradigm of scientific thinking. It is argued that the intellectual crisis and lack of clear perception of science and scientific thinking have been caused owing to, on one side, the refusal of the modern world to accept Truth and Reality of Life and the World and, on the other, True, Authentic and Universal Knowledge [the Islamic revelation]. Based on conjecture, speculation, imagination, fancies and desires peoples of the modern world have developed a worldview which is not in line with the Truth and Reality of Life and the world. Currently, the world, its systems and sub-systems, as a whole, are based on a false worldview. The false worldview has been instigated due to lack of clear perception of science and scientific thinking. It is maintained in this paper that the dominant paradigm of thinking, thought and action is based on speculation and conjecture instead of true scientific thinking. The Quran, in fact, challenges mankind and ask to adopt the framework of true scientific thinking; it invites people to think properly and follow the right method of scientific thinking based on True, Authentic and Universal Knowledge. It also challenges mankind and reminds them that until and unless they get rid of speculation and conjecture about the Life and the World, they would not be able to solve the problems of intellectual crisis and lack of clear perception of science and scientific thinking.